2018
DOI: 10.1093/mnras/sty096
|View full text |Cite
|
Sign up to set email alerts
|

The new lunar ephemeris INPOP17a and its application to fundamental physics

Abstract: We present here the new INPOP lunar ephemeris, INPOP17a. This ephemeris is obtained through the numerical integration of the equations of motion and of rotation of the Moon, fitted over 48 years of Lunar Laser Ranging (LLR) data. We also include the 2 years of infrared (IR) LLR data acquired at the Grasse station between 2015 and 2017. Tests of the universality of free fall are performed. We find no violation of the principle of equivalence at the 10 −14 level. A new interpretation in the frame of dilaton theo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(111 citation statements)
references
References 62 publications
2
106
0
3
Order By: Relevance
“…]∕ c is used to describe the oblateness (also called polar flattening) of the core, through its principal components of the MoI tensor  c ,  c , and  c ). While this allowed a close comparison to independent studies (Folkner et al, 2014;Pavlov et al, 2016), the previously reported (Viswanathan et al, 2018) uncertainty on f c does not account for uncertainties from considering a fixed value for c . A different plausible model value of c (e.g., 3 × 10 −4 ) would increase the corresponding value of f c by ≈ 2 × 10 −4 , suggesting an uncertainty Williams et al, 2014).…”
Section: Methodsmentioning
confidence: 75%
See 1 more Smart Citation
“…]∕ c is used to describe the oblateness (also called polar flattening) of the core, through its principal components of the MoI tensor  c ,  c , and  c ). While this allowed a close comparison to independent studies (Folkner et al, 2014;Pavlov et al, 2016), the previously reported (Viswanathan et al, 2018) uncertainty on f c does not account for uncertainties from considering a fixed value for c . A different plausible model value of c (e.g., 3 × 10 −4 ) would increase the corresponding value of f c by ≈ 2 × 10 −4 , suggesting an uncertainty Williams et al, 2014).…”
Section: Methodsmentioning
confidence: 75%
“…A set of Euler angles ( , , ) defines the orientation of the principal axes frame to the inertial (ICRF2) frame. The MoI of the Moon varies with time due to tidal distortions from the Earth, Sun, and spin distortion (Viswanathan et al, 2018). The component of permanent tide is included within the tidal and spin distortions (Williams et al, 2001).…”
Section: Contextmentioning
confidence: 99%
“…A net displacement of order dx ∼ 30 m incurred over 5 years may, at first glance, appear to be insignificant, but it has the same order of precision to which solar system ephemerides are currently determined. For example, the range residuals to the Cassini orbiter's telemetry reported by Fienga et al (2016) are of order dx ∼ 10−100 m, whereas the Martian range has been determined to within 3.6 m using just over one year of Mars Express data, and the lunar range to within 2 cm using 10 years of Apollo retro-reflector data from the Apache Point Observatory and 2 years of infrared lunar laser ranging data from the Grasse station (Viswanathan et al 2017(Viswanathan et al , 2018.…”
Section: The Case For a Tidal Acceleration Searchmentioning
confidence: 99%
“…It is recommended that the new radio telescope is colocated with a retroreflector, either a panel of cornercubes (Vasiliev et al 2014), or a next generation single cube retroreflector (Turyshev et al 2013;Araki et al 2016). Requiring no power on the Moon and no data transmission, the Earth-Moon laser ranging would help to determine the precise location of the station, and also independently contribute to study of lunar dynamics, and building of the lunar reference frame, and testing general relativity (Murphy 2013;Williams et al 2013b;Pavlov et al 2016;Viswanathan et al 2018).…”
Section: Co-locationmentioning
confidence: 99%
“…Later improvements, such as core flattening and dedicated parameters describing influence of Earth's tides to the orbit of the Moon, were implemented for DE430 ephemeris (Folkner et al 2014). The third publicly available lunar ephemeris, INPOP, is presently based on the same model (Viswanathan et al 2018).…”
Section: Lunar Dynamical Model and Ephemerismentioning
confidence: 99%